Linguistic creativity in music: Analyzing code-switching in the Acehnese regional pop songs - Afifuddin, Afifuddin; Murni, Sri Minda; Sumarsih, Sumarsih (Studies in English Language and Education, 2025)
This study explored the types of code-switching in Acehnese songs sung by Bergek, an Acehnese pop musician, and identified additional phenomena of code-switching beyond existing theoretical frameworks. The data consisted of ten purposively selected Bergeks songs collected from YouTube and Smule.com. The data were analyzed using a qualitative data analysis model that involves data condensation, data display, and conclusion drawing/verification. The data were categorized based on types of code-switching, including tag-switching (insertion of brief phrases or tags from one language into another), intra-sentential switching (the switch at the clausal, sentential, or word levels), and inter-sentential switching (alternation between clauses or sentences). The findings show that these three types of code-switching exist in Bergeks songs, with intra-sentential switching being the most prevalent (80 occurrences), reflecting the complex integration of multiple languages within a single sentence. Inter-sentential switching is the second most dominant type, observed 36 times. Tag-switching is the least common type identified, with only four occurrences. Interestingly, other notable patterns were also discovered, including affixation (the combination of Acehnese affixes with Indonesian base words) and phonemic fusion, where phonetic elements from different languages were blended. These patterns occurred 14 times in total. These findings provide a detailed view of the frequency and variety of code-switching in Bergeks songs, contributing to enhancing comprehension of language use in bilingual and multilingual musical contexts.